Myocardial angiopoietin-1 controls atrial chamber morphogenesis by spatiotemporal degradation of cardiac jelly - Kim, Kyun Hoo; Augustin, Hellmut (Cell reports, 2018)
The four-chamber structure of the mammalian heart is established during embryonic development. While key regulators for ventricular development are well studied, regulatory mechanisms for atrial chamber morphogenesis remain poorly understood. Here, we found that angiopoietin-1 (Angpt1), a vascular maturation factor, is highly and specifically expressed in atrial myocardium during heart development. Loss of myocardial Angpt1 in mouse embryo led to severe impairment in atrial chamber morphogenesis. We revealed that Angpt1 deficiency results in excessive deposition of cardiac jelly, which disturbs regulation of myocardial growth, thereby impairing maturation of atrial chambers. Mechanistically, myocardial Angpt1 activates endocardial Tie2 and positively regulates expression of ADAMTS proteases, which is crucial for proper degradation of cardiac jelly. Accordingly, loss of Tie2 also impairs ADAMTS-mediated degradation of cardiac jelly in atrium. Collectively, myocardial Angpt1/endocardial Tie2 signaling in atrium promotes spatiotemporal degradation of cardiac jelly during early cardiac development and is therefore indispensable for atrial chamber morphogenesis.
Gesehen am 18.10.2019